Glucose catabolism in liver tumors induced by c-MYC can be sustained by various PKM1/PKM2 ratios and pyruvate kinase activities - Méndez-Lucas, Andrés; Tschaharganeh, Darjus-Felix (Cancer research, 2017)
Different pyruvate kinase isoforms are expressed in a tissue-specific manner, with pyruvate kinase M2 (PKM2) suggested to be the predominant isoform in proliferating cells and cancer cells. Because of differential regulation of enzymatic activities, PKM2, but not PKM1, has been thought to favor cell proliferation. However, the role of PKM2 in tumorigenesis has been recently challenged. Here we report that increased glucose catabolism through glycolysis and increased pyruvate kinase activity in c-MYC-driven liver tumors are associated with increased expression of both PKM1 and PKM2 isoforms and decreased expression of the liver-specific isoform of pyruvate kinase, PKL. Depletion of PKM2 at the time of c-MYC overexpression in murine livers did not affect c-MYC-induced tumorigenesis and resulted in liver tumor formation with decreased pyruvate kinase activity and decreased catabolism of glucose into alanine and the Krebs cycle. An increased PKM1/PKM2 ratio by ectopic PKM1 expression further decreased glucose flux into serine biosynthesis and increased flux into lactate and the Krebs cycle, resulting in reduced total levels of serine. However, these changes also did not affect c-MYC-induced liver tumor development. These results suggest that increased expression of PKM2 is not required to support c-MYC-induced tumorigenesis in the liver and that various PKM1/PKM2 ratios and pyruvate kinase activities can sustain glucose catabolism required for this process. Cancer Res; 77(16); 4355-64. ©2017 AACR.
Gesehen am 25.09.2018